AN ANALYSIS CODE SWITCHING IN INSTAGRAM - Dara Deria Yunalizza; Manisa Laksana Putri; Muhammad Fatur Rizki Pratama; Giri Prayoga; Dhea Aura Cindiyana (Journal Of Language Education and Development (JLed), 2024)
This article aims to examine the use of Indonesian to English code switching in the Instagram application which focuses on explaining in more detail the conversations being conveyed.